2015
DOI: 10.3168/jds.2014-9174
|View full text |Cite
|
Sign up to set email alerts
|

The effect of microfiltration on color, flavor, and functionality of 80% whey protein concentrate

Abstract: The residual annatto colorant in fluid Cheddar cheese whey is bleached to provide a neutral-colored final product. Currently, hydrogen peroxide (HP) and benzoyl peroxide are used for bleaching liquid whey. However, previous studies have shown that chemical bleaching causes off-flavor formation, mainly due to lipid oxidation and protein degradation. The objective of this study was to evaluate the efficacy of microfiltration (MF) on norbixin removal and to compare flavor and functionality of 80% whey protein con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…A result of 12% norbixin destruction appears inconsistent with past studies, but previous studies have not addressed WPI. A large portion of the norbixin retained in the whey during the cheese make process is removed by microfiltration and discarded with the MF retentate (Qiu and others ). While the unbleached control was not chemically bleached, a study performed by Qiu and others () demonstrated that microfiltration reduced norbixin levels by approximately 40% in WPI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A result of 12% norbixin destruction appears inconsistent with past studies, but previous studies have not addressed WPI. A large portion of the norbixin retained in the whey during the cheese make process is removed by microfiltration and discarded with the MF retentate (Qiu and others ). While the unbleached control was not chemically bleached, a study performed by Qiu and others () demonstrated that microfiltration reduced norbixin levels by approximately 40% in WPI.…”
Section: Discussionmentioning
confidence: 99%
“…A large portion of the norbixin retained in the whey during the cheese make process is removed by microfiltration and discarded with the MF retentate (Qiu and others ). While the unbleached control was not chemically bleached, a study performed by Qiu and others () demonstrated that microfiltration reduced norbixin levels by approximately 40% in WPI. The liquid whey was bleached before MF, which reduced norbixin concentration in both the serum and fat phase of the liquid whey.…”
Section: Discussionmentioning
confidence: 99%
“…When used in the production of WPC 80 for norbixin removal, MF was as effective as HP but not as effective as the LP system. Both HP and LP bleached WPC 80 had higher cardboard and cabbage flavors compared with unbleached WPC 80 and a WPC 80 produced by microfiltration (Qiu et al, 2015).…”
Section: Alternatives To Chemical and Enzymatic Bleachingmentioning
confidence: 93%
“…Solvent-assisted flavor evaporation is also a good option because of its exhaustive volatile extraction and minimal thermal artifacts during isolation [98,99]. Many studies employed direct solvent extraction plus solvent-assisted flavor evaporation [20,21,23] or solid-phase microextraction [31,50,100,101] for determining off-aromas in dairy ingredients. The identification and quantitation of odorants, as previously discussed, is usually achieved through well-established flavor research instrumentation, such as gas chromatography-mass spectrometry (GC-MS), flame ionization detectors (GC-FIDs), or pulsed flame photometric detectors (GC-PFPDs) equipped with olfactometry.…”
Section: General Methodsmentioning
confidence: 99%